2008
DOI: 10.1097/gme.0b013e31815b644e
|View full text |Cite
|
Sign up to set email alerts
|

The role of hysteroscopy with eye-directed biopsy in postmenopausal women with uterine bleeding and endometrial atrophy

Abstract: Hysteroscopy is a significantly more accurate diagnostic method for the detection of endometrial pathology than TVS, has better specificity, and should be considered for all patients with AUB with an endometrial thickness of more than 4 mm. Hysteroscopy shows great efficiency in the diagnosis of focal abnormalities of the endometrium, which are unlikely recognized by ultrasonography and should be indicated in cases of AUB with an endometrial thickness less than 4 mm on ultrasonography because of the possibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
48
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 43 publications
7
48
1
2
Order By: Relevance
“…The mean ET was 5.76 ± 3.3877 mm with a range of 2.2-18 mm [7], and Tinelli et al [5]. In the present study, benign pathology (normal, atrophic, polyp, myoma) was diagnosed in 51.66 % out of which majority had atrophic endometrium.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The mean ET was 5.76 ± 3.3877 mm with a range of 2.2-18 mm [7], and Tinelli et al [5]. In the present study, benign pathology (normal, atrophic, polyp, myoma) was diagnosed in 51.66 % out of which majority had atrophic endometrium.…”
Section: Discussionsupporting
confidence: 53%
“…In present study, the sensitivity and specificity of TVS for suspecting endometrial pathology at ET B 4 mm were 87.09 and 75.86 %, respectively. Similar studies conducted by different investigators, Karlsson et al [2], Gull et al [3], Garuti et al [4] , Tinelli et al [5], and Kaur et al [6], had shown the sensitivity ranging from 89 to 100 % while specificity from 54.8 to 86 % at ET of 4 mm. In the present study, sensitivity, specificity, PPV, and NPV for Total 60 100…”
Section: Discussionsupporting
confidence: 49%
“…On this basis, office hysteroscopy could be considered a safe, well-tolerated diagnostic test that enables targeted endometrial biopsies because it accurately distinguishes normal endometrium from pathologic endometrium and has a better sensitivity, specificity, PPV and NPV than ultrasound (Garuti et al 1999, Taponeco et al 2002, Tinelli et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is abundant scientific evidence (Garuti et al 1999, Bronz 2000, Litta et al 2005, Guruwadayarhalli et al 2007, Tinelli et al 2008) that hysteroscopic examination is the gold standard for the management of AUB, with curettage of the uterine cavity required only for the treatment of haemostatic urgencies and when active bleeding is present.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Hysteroscopy provides direct visualization of the endometrium and direct endometrial biopsies may be obtained using office 5-mm operative hysteroscopy via miniaturized forceps. Hysteroscopy also allows the elimination of detected endometrial pathologies during the procedure such as intrauterine adhesions, submucous myomas or endometrial polyps.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%